2002
DOI: 10.1211/0022357021778349
|View full text |Cite
|
Sign up to set email alerts
|

Identification of indolyl-3-acryloylglycine in the urine of people with autism

Abstract: HPLC analysis of the urine of autistic subjects indicated the presence of an unidentified component in greatly increased concentrations. We have reported the isolation of this component by HPLC and its identification. Mass spectrometry, NMR and UV spectroscopy identified the peak as corresponding to indolyl-3-acryloylglycine (IAG, 3), and this has been confirmed by an independent synthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 12 publications
2
24
0
Order By: Relevance
“…Specimens were prepared and analysed blind and independently by highperformance liquid chromatography (HPLC) with UV diode-array detection (DAD) according to established protocols. [32][33][34][35] Analysis on urine fractions was executed for compounds co-eluting with exogenous opioid peptide standards and/or trans-indolyl-3-acryloylglycine (IAG).…”
Section: Methodsmentioning
confidence: 99%
“…Specimens were prepared and analysed blind and independently by highperformance liquid chromatography (HPLC) with UV diode-array detection (DAD) according to established protocols. [32][33][34][35] Analysis on urine fractions was executed for compounds co-eluting with exogenous opioid peptide standards and/or trans-indolyl-3-acryloylglycine (IAG).…”
Section: Methodsmentioning
confidence: 99%
“…IAG is a regular constituent of human urine and is produced by gut microflora (54,55) . It has been speculated that high levels of IAG in urine are an indication of gut dysbiosis (56) .…”
Section: Indolylacryloylglycinementioning
confidence: 99%
“…It has been speculated that high levels of IAG in urine are an indication of gut dysbiosis (56) . A few studies found increased levels of IAG in autistic individuals compared with asymptomatic controls (54,55) . Normally, tryptophan is catabolised to indole pyruvate and indole acetate and can be detected in the urine of normal subjects (57) .…”
Section: Indolylacryloylglycinementioning
confidence: 99%
“…In the context of proposed bowel and metabolism problems in autism some have suggested that the metabolite, indolyl-3-acryloylglycine (IAG), has been found in the urine of children with ASD, and may be a putative marker for autism and tryptophan metabolism problems (27). However, this study had no comparison to a control group to establish its specificity to the disorder.…”
Section: Introductionmentioning
confidence: 85%